Management of an Industry Standard Class in Vocational High Schools - Suroto Suroto; Nguyen Tien Hung (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
To remove a growing gap between students’ skills received in vocational high schools and real demands in the workforce, industries should be actively involved not only as external users but to work in curriculum development and learning evaluation. This study describes the process of planning, implementation, and supervision of an industry standard class resulted from collaboration between the school and the industry. This study was a qualitative study using data collection techniques of interviews, observation and documentation. The results revealed (1) the industry and the school were partners in planning the industry standard class including development of curriculum, facilities, infrastructure, teachers, and materials, (2) implementation of the class included theoritical and practical learning, and industry practices, (3) supervision was performed by the industry partner administrating industry standard competency tests, and (4) management of the class consisted of three sequenced stages namely selection of students in the third semester, implementation of industry standardized teaching and learning process from the third semester to the sixth semester, and a competency test in the sixth semester.